Prevalence of dental anxiety in relation to sociodemographic factors using two psychometric scales in Baghdad (Mustansiria Dental Journal, 2018)
Background: In spite of advances in dentistry, anxiety about dental treatment and thefear of pain remains public health problem and is a significant impediment todental treatment. The purpose of this study was to assess the levels of dentalanxiety in patients who referred to Al-Mustansiriyah dental clinics and Al-ShiekhOmar specialized dental center in Baghdad and their relation to their gender, age,educational level.Materials and methods: The study was done on (800) patients, aged (20-59) years inBaghdad. The survey form was prepared and translated from English to Arabiclanguages by certified translator and were filled by patients themselves withoutany help from dentists. Patients with mental retarded, those who not havingcompleted the survey form and those below 20 years and above 59 years wereexcluded. The survey was divided into 3 parts (socio-demographic information,Modified dental anxiety scale (MDAS) and Dental fear survey (DFS).Results: The present study showed that females had higher anxiety (13.57, 47.38)than males (8.98, 37.75) for Modified dental anxiety scale and Dental fear surveyrespectively. The anxiety decreased with advance of age (12.31, 11.41, 10.89,10.45 for Modified dental anxiety scale and 43.10, 41.22, 38.69, 37.93 for Dentalfear survey) in groups (1,2,3,4) respectively. The anxiety decreased with advanceof teaching, so the uneducated patients had higher mean of anxiety (14.45, 48.59)while the postgraduate patients had lower anxiety (9.10, 36.30) for Modifieddental anxiety scale and Dental fear survey respectively than others. There washigh significant difference between males and females at P-value (≤ 0.01) for bothModified dental anxiety scale and Dental fear survey scales.Analysis of variance (ANOVA) test showed high significant difference among agegroups and among education level groups at P-value (≤ 0.01) for both Modifieddental anxiety scale and Dental fear survey scales. The higher percentage ofanxiety scales was appeared in minimal anxiety score in males (56%, 48%) inModified dental anxiety scale and Dental fear survey respectively, while lessorpercentage was appeared in very high anxiety score in males (5.1%, 5.5%) inModified dental anxiety scale and Dental fear survey respectively. Pearson'scorrelation coefficient (R) showed that there was a positive relationship betweengender and anxiety scales, with statistically high significant at P-value (≤ 0.01).While, there was inverse relationship between age and anxiety scales, and between education and anxiety scales with statistically high significant at P-value (≤ 0.01)for both relations.Conclusion: The females had higher rate of anxiety than males. The anxietydecreased with advance of age and education level of patients. There was a strong(positive) relationship between gender and anxiety. While, there was inverse(negative) relationship between anxiety with age and education.